Organic Vegetables Marketing Model - Yompi, Berno; Handayawati, Hani Sri; Kusumawardani, Niniek Dyah (University of Brawijaya, 2020)
This research was conducted in Kurnia Kitri Ayu Farm (KKAF), Sukun Village, Sukun District, Malang City, East Java in 2019. The aim of this study is finding out the distribution channels of organic vegetables and margins or the distribution profits of Kurnia Kitri Ayu Farm organic vegetables distribution.The purposive sampling method was used in this study and the respondent was the owner of Kurnia Kitri Ayu Farm as an agribusiness actor. Data obtained in the field were analyzed by margin analysis, distribution and marketing share. The results showed that Kurnia Kitri Ayu Farm organic vegetable distribution channel involved partner farmers using three channels: 1) KKAF to distributors, supermarkets and final consumers, 2) KKAF to sales and final consumers and 3) KKAF to final consumers or Baby Porridge Company. The marketing distribution margin of KKAF organic vegetables was carried out starting from partner farmers of Rp. 5,000, - KKAF of Rp. 5,000 and supermarkets of Rp. 3,000, resulting in the increase of marketing margins between partner farmers, KKAF and supermarkets by Rp. 13,000. Then, between KKAF and salesman, each of them got a margin of Rp. 10,000, causing the distribution of the margin between partner farmers of Rp. 5,000, KKAF of Rp. 2,000, and salesman of Rp. 3,000. The market behavior of partner farmers resulted in a distribution margin of Rp. 5,000, KKAF of Rp. 2,000 and salesman of Rp. 5,000 caused a marketing margin position of the market behavior of partner farmers, KKAF and salesman that was Rp. 12,000.